P-99 CHARACTERIZATION OF PATIENTS WITH LIVER CIRRHOSIS, ITS COMPLICATIONS AND SURVIVAL. - Dayron Páez Suárez; Juan Ramón Pineda Paz; Mayra Zoa Más Martínez; Enrique Rogelio Arús Soler; Gabriel Gonzalo Astorga Moreno; Rhonda Savitri Mohan (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: The complications of liver cirrhosis significantly influence the survival of these patients.Objective: Characterize patients with liver cirrhosis, its complications and survival. Patients / Materials and Methods: Longitudinal prospective study in the Gastroenterology service in a tertiary hospital of national reference. Period: December 2017 - December 2019. Sample: 52 patients who met selection criteria. Clinical variables were recorded to determine the stage of cirrhosis, the Child‐Pugh and the complications presented. Data were summarized, association between variables was evaluated, and survival was estimated. Results and Discussion: The average age was 59 ± 11.0 years, men predominated (57.7%), alcohol consumption as the most frequent etiology (53.3%), ascites decompensation as the debut form (55.8%) and complication most incident (75%) followed by jaundice (40.4%) and encephalopathy (28.8%). F1 esophageal varices were the most confirmed endoscopic finding (26.9%), with stage 4 cirrhosis (69.2%) and Child-Pugh B (55.8%) predominating in the sample. At the end of the study, 19.2% of the patients died, overall survival was 89.0% at one year and 55.1% at two years, the association of the Child-Pugh scale as a predictor of mortality being statistically significant. Conclusions: An association was demonstrated between the causes of cirrhosis and sex, mainly alcohol in men. One fifth of the patients died and overall survival showed a notable decrease at one year and two years, the estimate of survival according to the Child-Pugh scale being significant.